2013
DOI: 10.1016/j.jcv.2013.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and molecular analysis of noroviruses RNA in blood from children hospitalized for acute gastroenteritis in Belém, Brazil

Abstract: Detection and molecular characterization of NoVs GII in paired stool and serum samples suggest that the dissemination of NoVs to the blood stream is not uncommon, but the role of viruses spread outside the gut and the relationship with disease severity need to be further addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Long-term NoV excretion and chronic diarrhea have been previously reported in other studies, mainly in immunocompromised and/or transplanted patients [25,30,31]. Prior to this study, long-term viremia had not yet been investigated, even though NoV had been detected in the blood of children with acute gastroenteritis [32,33].…”
Section: Discussionmentioning
confidence: 63%
“…Long-term NoV excretion and chronic diarrhea have been previously reported in other studies, mainly in immunocompromised and/or transplanted patients [25,30,31]. Prior to this study, long-term viremia had not yet been investigated, even though NoV had been detected in the blood of children with acute gastroenteritis [32,33].…”
Section: Discussionmentioning
confidence: 63%
“…In Brazil, GII.4 NoV is most frequently reported from emergency departments [5,6,29,30]. The presence of a variety of genotypes in Sergipe and the periodic shift of GII.4 variants (i.e., GII.4 New-Orleans_2009 and GII.4 Sydney_2012) reflects the emergence worldwide of GII.4 variants [29,[31][32][33][34][35][36], confirming that the NoV genotypes have a wide geographical distribution.…”
Section: Discussionmentioning
confidence: 95%
“…There is also limited knowledge of the pathogenesis of human NoV infection. Children, immunocompromised adults, and gnotobiotic pigs and calves used as models of human NoV infection all can develop NoV viremia (2)(3)(4)(5)(6)(7), suggesting that NoV infection may not be limited to the gut. However, no data on NoV viremia in immunocompetent adults exist.…”
mentioning
confidence: 99%
“…SMV-infected subjects had 1 sample tested per subject, selected from the day of peak viral shedding in stool. Our sample was large enough to detect an absence of viremia with more than 95% power, alpha ϭ 0.05, and assuming a null hypothesis of at least 15% of subjects with viremia, a lower rate than that seen in pediatric NoV or gnotobiotic models (2,3,6,7). Serum samples were taken on the days of greatest viral shedding in stool, as quantified by reverse transcription-PCR (RT-PCR) (10), because a past study identified higher fecal NoV load in children with viremia, leading us to assume that days of highest NoV shedding in stool would be most likely to be associated with viremia (3).…”
mentioning
confidence: 99%